Herd behavior in Malaysian capital market: An empirical Analysis - Duasa, Jarita; Kassim, Salina H. (Reprograph Craiova Publishers, 2009)
This study examines the existence of herd behavior among foreign investors in the Malaysian capital market. In methodology, the study analyzes the herd behavior by estimating vector error correction (VECM) model of FPI inflows as well as FPI outflows from/to major investors such as the United States, United Kingdom, Singapore and Hong Kong using quarterly data covering the period of Q1:1991 to Q3:2007. Additionally, we adopt an innovation accounting by simulating variance decompositions (VDC) and impulse response functions (IRF) for further inferences. The findings support the belief that there is a strong herd instinct prevailing among foreign investors in the Malaysian capital market.